Walk off winning a game plan for leading your team and organization to success - Trimper, Steve 1970- (John Wiley & Sons, Inc., 2020)
"There are many books available on the topic of leadership. But there are not many written by an author who has taken their extensive leadership experience with high level sports and applied it to the business world. Though many interviews, failures and successes, Trimper has come up with key principles related to team building, culture, and organization building. Walk Off Winning gives readers the motivation and strategies to?become a doer? This book is for anyone involved in leadership, sports management, and the general business world. Filled with inspirational anecdotes and honest advice, this is a much sought-after guide for leaders of all kinds"--
Includes index. - Online resource; title from digital title page (viewed on March 04, 2020)
Keywords: Leadership; Teams in the workplace -- Management; Success in business; Équipes de travail; Gestion; Succès dans les affaires; BUSINESS & ECONOMICS; Leadership; Teams in the workplace; Management